PENGARUH MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DI KELAS XI AKL SMKN 3 PADANG - Yusti, Annisa Hulhusna (Departemen Matematika, 2024)
The study's overarching goal is to compare and contrast the conceptual understanding of students taught using the STAD learning paradigm with that of students taught using more traditional approaches. Only a randomized control group was utilized in this quasi-experimental study. Class XI AKL students from all three years of the 2024–2025 school year at SMK Negeri 3 Padang made up the study's population. We used a basic random sampling procedure to pick our sample. The information collected for this study came from seven essay problems on the final exam and six quizzes. The data analysis method includes looking at the session quizzes and then utilizing a t-test to examine the final exam.The null hypothesis (H0) was rejected as a result of the significant P-value of 0.007 that was produced by the last test of hypothesis testing. Students that use the STAD learning model appear to have a better grasp of mathematical concepts than their counterparts who use more conventional learning models.Keywords– Concept Understanding, Student Teams Achievement Divisions, Quasi-experiment